MOLECULAR EPIDEMIOLOGY OF MULTIDRUG- AND EXTENSIVELY DRUG-RESISTANT TUBERCULOSIS IN KANO STATE, NORTHWESTERN NIGERIA - Adamu, Ado Umar; Said, Nasir Rabiu; Lamido, Ummussalama Kabir; Abdullahi, Amina; Taura, Dalha Wada; Mukhtar, Muhammad Dauda; Rogo, Lawan Dahiru; Ahmad, Umar Aliyu; Bawa, Musa K.; Mustapha, Tukur; Dawaki, Salwa Shehu; Fagge, Hamza Shuaibu; et al. (FUDMA Journal of Sciences, 2025)
Tuberculosis (TB) remains a major global public health challenge, and Nigeria is among the eight countries that contribute the highest burden of casesThe emergence and rise of multidrug-resistant (MDR) and extensively drug-resistant (XDR) TB threaten progress toward elimination, yet molecular epidemiological data from northwestern Nigerian states remain limited. The objective of this study was to determine the prevalence and molecular determinants of MDR- and XDR-TB among GeneXpert-positive pulmonary TB patients in Kano State using MTBDRplus and MTBDRsl assays. A cross-sectional study was conducted using samples collected from 401 GeneXpert-positive TB patients recruited across 19 DOTS clinics in Kano State between 2018 and 2019. Sputum samples were cultured on Lowenstein–Jensen medium, followed by molecular drug susceptibility testing with the Genotype MTBDRplus (first-line resistance) and MTBDRsl (second-line resistance) assays. Socio-demographic and clinical data were obtained via structured questionnaires. Multidrug-Resistant Tuberculosis (MDR-TB) was detected in 41 patients (10.2%), while rifampicin and isoniazid mono-resistance occurred in 26 (6.5%) and 6 (1.5%), respectively. Resistance clustered in urban LGAs, notably Nasarawa (3.5%), Fagge (1.5%), and Gwale (0.7%). MDR-TB was most prevalent among males (11.5%) and patients aged 25–34 years (35.4%).There was no significant association between HIV status and MDR-TB (HIV-positive: 9.8%; HIV-negative: 10.3%). Second-line resistance showed fluoroquinolone resistance in 6 (1.5%), aminoglycoside resistance in 12 (3.0%), and low-level amikacin resistance in 1 (0.2%). Two XDR-TB cases (0.5%) were identified in Nasarawa and Ungogo LGAs. The MDR-TB burden in Kano State is high, with urban hotspots and emerging XDR-TB, requiring strengthened surveillance, targeted interventions, and rational antibiotic...
Keywords: Multidrug-resistant tuberculosis; Extensively drug-resistant tuberculosis; Molecular epidemiology; MTBDRplus/MTBDRsl assays; Kano; Nigeria